2022
DOI: 10.1101/2022.01.31.478526
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A second DNA binding site on RFC facilitates clamp loading at gapped or nicked DNA

Abstract: Clamp loaders place circular sliding clamp proteins onto DNA so that clamp-binding partner proteins can synthesize, scan, and repair the genome. DNA with nicks or small single-stranded gaps are common clamp-loading targets in DNA repair, yet these substrates would be sterically blocked given the known mechanism for binding of primer-template DNA. Here, we report the discovery of a second DNA binding site in the yeast clamp loader Replication Factor C (RFC) that aids in binding to nicked or gapped DNA. This DNA… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…[ 31,32,50 ] Consistent with a role in gap repair, the recent cryoEM data also reveal that RFC can even unwind dsDNA at both the internal and external DNA binding sites. [ 31,50 ] There appear to be two separation pins(for 3′ [Trp638 and Phe582] and 5′ [His556 and His659] ends) that may coordinate with each other at a nick to unwind up to five nucleotides of duplex DNA for clamp loading. [ 24 ]…”
Section: Rfc Binds Dna With Nicks or Small Gaps Using Two Dna Sites T...mentioning
confidence: 90%
See 2 more Smart Citations
“…[ 31,32,50 ] Consistent with a role in gap repair, the recent cryoEM data also reveal that RFC can even unwind dsDNA at both the internal and external DNA binding sites. [ 31,50 ] There appear to be two separation pins(for 3′ [Trp638 and Phe582] and 5′ [His556 and His659] ends) that may coordinate with each other at a nick to unwind up to five nucleotides of duplex DNA for clamp loading. [ 24 ]…”
Section: Rfc Binds Dna With Nicks or Small Gaps Using Two Dna Sites T...mentioning
confidence: 90%
“…The 5′ DNA site of Rfc1 is not required for cell viability but mutations or deletions of the BRCT result in defective gap repair. [ 49–51 ] The possibility that RFC binds a DNA gap, via the BRCT region's ability to bind a recessed 5′ end, along with the 3′ primer terminus in the central chamber of the entire clamp loader, became obvious from the external DNA binding site in the Rad24‐RFC−9‐1‐1 structures. [ 45,46 ] Recent structures from three different labs have shown that this is indeed the case as illustrated in Figure 5.…”
Section: Rfc Binds Dna With Nicks or Small Gaps Using Two Dna Sites T...mentioning
confidence: 99%
See 1 more Smart Citation